For \( f(x)=x^{2}+2 \) and \( g(x)=\sqrt{4-x} \), find a. ( \( f \circ g)(x) \); b. the domain of \( f \circ g \) a. ( \( f \circ g)(x)=6-x \) (Simplify your answer.) b. What is the domain of \( f \circ g ? \) ? The domain is (Simplify your answer. Type your answer in interval notation. Use integers the expression.)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To find \( (f \circ g)(x) = f(g(x)) \), we start by substituting \( g(x) \) into \( f(x) \). 1. First, compute \( g(x) = \sqrt{4 - x} \). 2. Now substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(\sqrt{4 - x}) = (\sqrt{4 - x})^2 + 2 = (4 - x) + 2 = 6 - x. \] So, \( (f \circ g)(x) = 6 - x \). To determine the domain of \( f \circ g \): 1. The function \( g(x) = \sqrt{4 - x} \) is defined when \( 4 - x \geq 0 \), which simplifies to \( x \leq 4 \). 2. Since \( g(x) \) outputs values for \( x \leq 4 \), and there are no additional constraints from \( f(x) \), the domain of \( f \circ g \) is determined solely by \( g(x) \). Thus, the domain of \( f \circ g \) is \( (-\infty, 4] \).